Ensaios sobre o impacto da pandemia no mercado de trabalho: uma análise dos fatores que afetaram a jornada de trabalho - Freitas, Thiago de Araújo (2024)
The global health crisis triggered by COVID-19 in December 2019 and felt by the country by late March 2020 had a profound impact on the Brazilian economy, still in the process of recovering from the economic recession experienced between 2015 and 2016. This period not only interrupted the economic recovery but also highlighted structural vulnerabilities in the country's healthcare systems and economy. The country faced challenges such as temporary closure of businesses, significant reduction in economic activity, alarming increase in unemployment, and implementation of reduced work hours. In this context, three essays on the pandemic's impact on the labor market comprise this thesis. The first chapter discusses the effects of workers' migration to the informal sector on working hours following the onset of the pandemic. For this purpose, an extensive literature review is conducted to understand the impacts of the pandemic and the main factors that led to formal job losses. Using the Difference-in-Differences methodology and data from the quarterly continuous PNAD, this study compared the working hours of individuals who were forced to migrate to informality with a counterfactual scenario, in which they would remain employed in the formal sector of the economy, through the use of a control group. The results indicate a significant reduction in the working hours of workers who left formal jobs. The second chapter investigates the role of families in labor supply during the pandemic, analyzing the working hours of married individuals compared to a counterfactual scenario in which they would be single. Using the Propensity Score Matching method and PNAD COVID- 19 data to construct the control group, this study reveals distinct results when separately analyzing in-person work and remote work. It is indicated that married women tend to reduce their working hours compared to singles, with this difference being more significant among those in in-person work. On the other hand, for men, being in a marriage implies working more hours than if they were single. These results highlight the presence of a gender bias in labor supply during social isolation situations. The third and final chapter is dedicated to understanding how school closures and restrictions in the labor market created obstacles for young people to reconcile their occupational choices between work and study during the pandemic. Additionally, it seeks to analyze the role of income transfer programs in these decisions. A multinomial logit model was used with PNAD COVID-19 data for the four possible occupational choices. The results indicate that receiving Emergency Aid increased the probability of young people neither working nor studying compared to the option where they only work. On the other hand, being a beneficiary of the Bolsa Família program increased the chances of young people being exclusively employed. Factors such as gender, age, race, maternal education level, and family support played determining roles in these choices.